2020
DOI: 10.1016/j.htct.2019.10.003
|View full text |Cite
|
Sign up to set email alerts
|

Craniofacial geometric morphometrics in the identification of patients with sickle cell anemia and sickle cell trait

Abstract: Objective The aims of this study were to identify the main characteristics regarding the shape and size of the craniofacial region in patients with sickle cell anemia (SCA) and sickle cell trait (SCT) and in unaffected patients using geometric morphometrics and to check the efficiency of this method. Material and Methods A cross-sectional analytical study of 45 patients (15 in each group) was performed. Lateral radiographs of the skull were used for the analysis. Sevent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 18 publications
0
3
0
2
Order By: Relevance
“…According to Nunes et al, (2018) (16) , it is possible identifying elderly individuals with diagnostic of diabetes and high blood pressureboth diseases or no illness at all -based on the morphology of the right side of the face by using geometric morphometrics. Ferreita et al, (2019) (13) found differences in the telemetry of patients with sickle cell anemia, non-affected sickle cell trait; this outcome shows that the geometric morphometrics is more effective than conventional anthropometry.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…According to Nunes et al, (2018) (16) , it is possible identifying elderly individuals with diagnostic of diabetes and high blood pressureboth diseases or no illness at all -based on the morphology of the right side of the face by using geometric morphometrics. Ferreita et al, (2019) (13) found differences in the telemetry of patients with sickle cell anemia, non-affected sickle cell trait; this outcome shows that the geometric morphometrics is more effective than conventional anthropometry.…”
Section: Discussionmentioning
confidence: 97%
“…Geometric morphometrics (GM) is a tactic adopted for human health diagnostics, since it uses quantitative approach to assess changes and variations in the shape of individuals' morphologic structures -it allows describing the association between diseases and the human body (12,13) . It represents a method with the potential to assess the effects of environmental factors and diseases on organs and organisms (14) .…”
Section: Discussionmentioning
confidence: 99%
“…Ferreira WB (2020) also stated similar findings in Craniofacial geometric morphometrics in the identification of patients with sickle cell anemia and sickle cell trait. [ 10 ]…”
Section: Discussionmentioning
confidence: 99%
“…Alguns desses pontos de referência foram escolhidos de modo a corresponder aos comumente já utilizados em sistemas cefalométricos tradicionais na análise de radiografias cefalométricas laterais, familiares à maioria dos cirurgiões-dentistas, principalmente ortodontistas, para determinação de maloclusão (Wellens, Kuijpers-Jagtman & Halazonetis, 2013). Além disso, alguns desses também já foram utilizados em outros estudos (Woon et al, 2019;Ferreira, Nunes, Pithon, Maia & Casotti, 2020;Pereira, Silva, Assis, Casotti & Nunes, 2021). A Tabela 1 descreve os marcos e os semimarcos anatômicos utilizados.…”
Section: Materiais E Métodosunclassified